2016
DOI: 10.1016/j.apcatb.2015.06.047
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated self-cleaning by Cu promoted semiconductor binary-oxides under low intensity sunlight irradiation

Abstract: a b s t r a c tUniform adhesive TiO 2 -ZrO 2 films co-sputtered on polyester (PES) under low intensity sunlight irradiation discolored methylene blue (MB) within 120 min. The discoloration kinetics was seen to be accelerated by a factor four by TiO 2 -ZrO 2 -Cu containing ∼0.01% Cu, as determined by X-ray fluorescence (XRF). TiO 2 -ZrO 2 -Cu also increased also accelerated by a factor the discoloration of MB compared to TiO 2 /Cu(PES). MB discoloration was also monitored under visible light in the solar cavity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 41 publications
1
12
0
1
Order By: Relevance
“…A corto o mediano plazo, esta interacción provoca el deterioro de las ECR, generando además gastos anuales entre 18 a 21 mil millones de USD en rehabilitaciones o reparaciones debido a la corrosión del acero de refuerzo (Barnat-Hunek et al, 2016;Khaloo et al, 2016). Más del 50% de estas ECR presentan problemas de deterioro a causa de la alta permeabilidad o baja calidad del concreto (Fajardo, et al, 2015;Rtimi et al, 2016), que favorece al mecanismo de transporte de agentes agresivos como al dióxido de carbono (CO2), ion cloruro (Cl-) y sulfatos (SO4-2), siendo éstos, la principal causa de deterioro en las ECR (Achal et al,2015;Trapote-Barreira et al, 2014). Sin embargo, debemos recordar que las propiedades importantes, tales como la resistencia, la permeabilidad y la durabilidad, están ligadas directamente con la porosidad en el concreto (Fajardo et al, 2015;Hou et al, 2015;Hou et al, 2016;Kupwade-patil et al, 2016).…”
Section: Introductionunclassified
“…A corto o mediano plazo, esta interacción provoca el deterioro de las ECR, generando además gastos anuales entre 18 a 21 mil millones de USD en rehabilitaciones o reparaciones debido a la corrosión del acero de refuerzo (Barnat-Hunek et al, 2016;Khaloo et al, 2016). Más del 50% de estas ECR presentan problemas de deterioro a causa de la alta permeabilidad o baja calidad del concreto (Fajardo, et al, 2015;Rtimi et al, 2016), que favorece al mecanismo de transporte de agentes agresivos como al dióxido de carbono (CO2), ion cloruro (Cl-) y sulfatos (SO4-2), siendo éstos, la principal causa de deterioro en las ECR (Achal et al,2015;Trapote-Barreira et al, 2014). Sin embargo, debemos recordar que las propiedades importantes, tales como la resistencia, la permeabilidad y la durabilidad, están ligadas directamente con la porosidad en el concreto (Fajardo et al, 2015;Hou et al, 2015;Hou et al, 2016;Kupwade-patil et al, 2016).…”
Section: Introductionunclassified
“…The position of the potential energy level of the Cu-intra-gap states lies between the TiO 2 vb (3.1 eV) and the TiO 2 cb (À0.1 eV) and can be estimated to be close to 0.15 eV [19]. The Cu 1+/2+ on the TiO 2 under band-gap irradiation would work as an electron acceptor enhancing MB-degradation [20]. Fig.…”
Section: Rr@tio 2 -Cu Microstructure: Surface Propertiesmentioning
confidence: 99%
“…Reaction (2) is much faster than the CuO dissolution [19,20], shown in Eq. EDTA is used generally as a hole scavenger in TiO 2 photocatalysis.…”
Section: Mb Discoloration Kineticsmentioning
confidence: 99%
“…inactivation. These studies have shown a drastic enhancement of the bacterial inactivation kinetics of E. coli when Cu was added to binary-oxides in percentages from 0.01% (decoration) up to 1% (doping) [119,127,173]. A variety of TiO2-Cu preparations and the evaluation of their activity for diverse applications is an area of current interest [129][130][131]174].…”
Section: Interfacial Charge Transfer (Ifct) Suggested On Tio2-cu Filmmentioning
confidence: 99%